Feasibility Study of the CT Clock, a Method for Estimating Onset Time and Brain Tissue Viability After Ischemic Stroke - Grant Mair; William Whiteley; Francesca Chappell; Anuka Boldbaatar; Sarah Risbridger; Allan MacRaild; Joanna M. Wardlaw (Journal of Stroke Medicine, 2026)
Introduction When ischemic stroke onset time is unknown, eligibility for thrombolysis and thrombectomy requires computed tomography (CT) perfusion or magnetic resonance imaging, but often only nonenhanced CT is available. We have developed a method for estimating ischemic stroke onset time and brain tissue viability from nonenhanced CT alone, the CT Clock. We aim to test the feasibility of frontline clinicians using the CT Clock acutely. Participants and Methods Prospective single-center feasibility study. We recruited patients during normal working hours with ischemic stroke, excluding lacunar syndrome and minor stroke (National Institutes of Health Stroke Scale [NIHSS] ≤ 4). We recruited stroke clinicians and radiologists to apply the CT Clock (measure ischemic lesion attenuation) in the acute setting. Primary endpoint: proportion of clinicians successfully using the CT Clock. We assessed ease of use on Likert scales (1 = easy to 5 = hard) and time taken. Results We recruited 95 clinicians: 73 radiologists and 22 stroke clinicians; 51 were consultants, and 44 were in training. We recruited 35 patients in 12 months: 23 were male (66%), the median age was 69 years (interquartile range [IQR] 58-72); the median NIHSS 8 (IQR 6-15), scanned at a median of 113 min after stroke. Clinicians provided 130 CT Clock assessments, with a median of three per patient. All attempts were successful. Clinicians found it easy to find (median 2, IQR 1-3) and measure (median 1, IQR 1-2) ischemic lesions ( n = 72). Most assessments (120/130, 92%) took